Daya Saing Ekspor Gula Kelapa Kristal Indonesia di Pasar Internasional - Satriani, Ratna; Tri Raditya, Fanny (CV. Kalimasada Group, 2025)
International trade can be defined as trading activities carried out by residents of a country with residents of other countries based on mutual agreements. Crystal coconut sugar is Indonesia's leading export product and is the second-largest export in the world. The increase in world consumption of crude palm oil is an opportunity for Indonesia to increase exports of crystal coconut sugar. This study aims to: (1) Determine the position of the competitiveness of Indonesia's crystal organic exports in the international market, (2) Determine the competitiveness of Indonesia's crude palm oil exports whether it shows a po sitive or negative trend, (3) Knowing the export performance of Indonesia Crystal coconut sugar in Indonesia. International market. This research was conducted from March 20 to April 9, 2024. The object of this research is the export of Indonesian crystal coconut sugar (HS code 151311). The analysis used in this research is the Revealed Comparative Advantage (RCA) analysis, the Export Competitiveness Index (ECI), and the Products Mapping. The results showed that Indonesia's exports were in group A, which means that they have a comparative advantage with export specialties. The export competitiveness of Indonesian Crystal coconut sugar shows a positive trend of competitiveness. The results of the TBI analysis show that Indonesia is a country that specializes in exporting Crystal coconut sugar.